Effect of nutrient reductions on dissolved oxygen and pH: a case study of Narragansett bay - Hongjie Wang; Daniel L. Codiga; Heather Stoffel; Candace Oviatt; Kristin Huizenga; Jason Grear (Frontiers in Marine Science, 2024)
To assess the consequences of nutrient reduction strategies on water quality under climate change, we investigated the long-term dynamics of dissolved oxygen (DO) and pH in Narragansett Bay (NB), a warming urbanized estuary in Rhode Island, where nitrogen loads have declined due to extensive wastewater treatment plant upgrades. We use 15 years (January 2005-December 2019) of measurements from the Narragansett Bay Fixed Site Monitoring network. Nutrient-enhanced phytoplankton growth can increase DO in the upper water column while subsequent respiration can reduce water column DO and enhance bottom water acidification, and vice-versa. We observed significant decreases in surface DO levels, concurrent with a significant increase in bottom DO, associated with the nitrogen load reduction. Surface DO decline was primarily attributed to reduced intensity of primary productivity, supported by a concurrent decrease in surface chlorophyll concentrations. Meanwhile, the influence of reduced organic matter respiration led to the increase of bottom DO levels by 9 µmol kg -1 (approximately 0.2 mg L -1 for typical summer temperature and salinity) over a 15-year period, which overcame the opposite influence of oxygen reduction from solubility decreases due to warming temperatures. In contrast, long-term changes in surface pH have not exhibited discernible trends beyond natural variability, likely due to the complex and sometimes opposing influences of biological activity and changing river flow conditions. We observed a slight increase in bottom pH, associated with the increase in DO in bottom water. Notably, future variations in freshwater discharge, particularly linked to extreme precipitation events, may further influence water carbonate chemistry and thereby impact pH dynamics. This study highlights the necessity of long-term time series measurements in helping understand the impacts of environmental management practices in improving water quality in coastal regions during a changing climate.

Managed Nitrogen Load Decrease Reduces Chlorophyll and Hypoxia in Warming Temperate Urban Estuary - Daniel L. Codiga; Heather E. Stoffel; Candace A. Oviatt; Courtney E. Schmidt (Frontiers in Marine Science, 2022)
Many urban estuaries worldwide suffer from excess phytoplankton and hypoxia (low oxygen) due to high nutrient loads. A common water quality management strategy is to require wastewater treatment facility upgrades. This case study examines Narragansett Bay, a warming temperate mid-latitude urban estuary with seasonal periodic hypoxia, during June through September from 2005 to 2019. Within this period, numerous facilities were upgraded to nitrogen removal over several years. The response of the bay is more consistent with “textbook” expectations for reduced chlorophyll and hypoxia than what was seen in many other systems—despite its complex coastline geometry, numerous river inputs, and widely-distributed treatment facilities. River flow drives inter-annual variability with increased load, density stratification, chlorophyll, and hypoxia in wet years. Mean 2013-2019 bay-wide total nitrogen load was 34% less than the 2005-2012 mean, a reduction of about 10 6 kg yr-1, comparable to the range of flow-driven inter-annual variations. Chlorophyll Index and Hypoxia Index event-based metrics applied to high-frequency time series observations at eight sites quantify exceedances of severe and moderate thresholds. Relatively steady 33% and 16% Chlorophyll Index declines, for severe and moderate thresholds, occurred from about 2007 to 2019. The Hypoxia Index declined markedly by 2009 and 2014 for severe and moderate thresholds, respectively, and remained at or near zero from 2014 to 2019. The load reduction explains chlorophyll and hypoxia declines better than physical processes including river flow, stratification, tidal variations, winds, sea level differences, and temperatures. River flow about 55% higher than the 2005-2019 mean would increase non-treatment facility loads by an amount comparable to the managed load decrease, so future wet summers could partially reverse the improvements. Long-term trends include warming of about 0.5°C decade -1 , which reduces oxygen saturation by 0.1 mg l -1 decade -1 . This rate is likely a lower bound for temperature-driven oxygen decreases, because warming can also accelerate phytoplankton growth and bacterial consumption. Without warming, the managed load decrease would have curtailed hypoxia more effectively. Climate trends should be at least as important to future eutrophication as the managed load decline because, in addition to warming influences, long-term increases in river flow would increase load and stratification.

Narragansett Bay Hypoxic Event Characteristics Based on Fixed-Site Monitoring Network Time Series: Intermittency, Geographic Distribution, Spatial Synchronicity, and Interannual Variability - Daniel L. Codiga; Heather E. Stoffel; Christopher F. Deacutis; Susan Kiernan; Candace A. Oviatt (Estuaries and Coasts, 2009)